Contrastive Analysis of Mother Concept in English and Uzbek Languages - Bobokhanov Temur Bahriddinovich (Periodica Journal, 2024)
This article analysis of English and Uzbek folk paremiological proverbs are analyzed cross-sectionally. In this article, the expression of the concept of the homeland in proverbs, their meaningful field, their meanings in this field, and the parems summarizing the national values of the people are analyzed.
Keywords: people; Paremiological unit; proverb; concept